JOURNAL OF GOVERNMENT & POLITICS : The Role of Islamic Faith-Based Organization in Building Solidarity and Resilience among People of Different Faiths in Northeast Thailand - Imron Sohsan (FISIPOL UMY, 2014)
The purpose of this paper are to examine the role of FEDMIN in building solidarity and resilience between Muslims and Buddhists and to find a model of peaceful coexistence among people of different faiths in northeast Thailand called "isan region."